2001
DOI: 10.1207/s15327906mbr3604_05
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Cognitive Abilities as a Function of Level of General Intelligence: A Latent Variable Approach

Abstract: Differentiation of cognitive abilities at different levels of general ability in same-aged subjects was tested by a latent variable approach in a multiple-groups design. Eighteen-year old conscripts (n = 14,720) representing the whole range of general ability in the male population, except for the mentally retarded, were tested by the Swedish Enlistment Battery. The sample of subjects was divided into 8, 16 and 32 groups according to level of general ability (G), and the amount of variance due to the ability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
0
25
1
3
Order By: Relevance
“…The inverse relationship between IQ and strength of subtest correlations has been confirmed many times during the last fifteen years (e.g., Abad, Colom, JuanEspinosa, & García, 2003;Carlstedt, 2001;Detterman, 1993;Detterman & Daniel, 1989;Evans, 1999;Facon, 2002Facon, , 2003aHunt, 1997;Jensen, 2003;Legree, Pifer, & Grafton, 1996;Lynn, 1990), and it is now considered practically a fact that remains only to be explained. Some studies (e.g., Fogarty & Stankov, 1995;Hartmann & Teasdale, 2004;Nesselroade & Thompson, 1995) have also given less support to the inverse relationship, and these also require an explanation.…”
mentioning
confidence: 85%
“…The inverse relationship between IQ and strength of subtest correlations has been confirmed many times during the last fifteen years (e.g., Abad, Colom, JuanEspinosa, & García, 2003;Carlstedt, 2001;Detterman, 1993;Detterman & Daniel, 1989;Evans, 1999;Facon, 2002Facon, , 2003aHunt, 1997;Jensen, 2003;Legree, Pifer, & Grafton, 1996;Lynn, 1990), and it is now considered practically a fact that remains only to be explained. Some studies (e.g., Fogarty & Stankov, 1995;Hartmann & Teasdale, 2004;Nesselroade & Thompson, 1995) have also given less support to the inverse relationship, and these also require an explanation.…”
mentioning
confidence: 85%
“…When consulting the literature the majority of studies support SLODR (ability) (e.g., Abad, Colom, Juan-Espinosa, & Garcia, 2003;Baumeister & Bartlett, 1962;Birren, 1952;Carlstedt, 2001;Coyle, 2002;Deary et al, 1996;Der & Deary, 2002;Detterman & Daniels, 1989;Detterman et al, 1992;Evans, 1999;Filella, 1960;Jäger, 1964;Jäger & Todt, 1964;Jensen, 2003;Kane, 2000;Legree, Pifer, & Grafton, 1996;Lienert, 1961Lienert, , 1964Lienert & Faber, 1963;Lynn, 1992;Lynn & Cooper, 1993, 1994Mitchell, 1956;Maxwell, 1972;Nesselroade & Thompson, 1995;Reinert, Baltes, & Schmidt, 1965;Segel, 1948;Spearman, 1927;Wewetzer, 1958) but some studies either find no difference in g saturation or find the opposite pattern (Amelang & Langer, 1968;Bloom et al, 1988;DeVoss, 1926;Eyferth, 1963;Facon, 2004;Fogarty & Stankov, 1995;Hartmann & Teasdale, 2004, accepted for publication; Roesslein, 1953). However, not all studies are equally valid and it is therefore necessary to look at the individual studies in order to investigate whether the specific study controls for potential confounders.…”
Section: Literature On Slodr (Ability)mentioning
confidence: 99%
“…Two of the more well-known differentiation hypotheses are the cognitive-differentiation hypothesis and the age-differentiation hypothesis. The cognitive-differentiation hypothesis posits that abilities become increasingly distinct at higher levels of general intelligence (e.g., Carlstedt, 2000;Detterman & Daniel, 1989, see also Spearman, 1927). For example, Abdad, Colom, Juan-Espinosa, and García, (2003) recently demonstrated that the g factor accounts for more variance among less able individuals than it does among more able individuals, and that the average correlation among ability tests is greater for low ability individuals than it is for high ability individuals.…”
Section: Differentiation Of Abilities As a Function Of Neuroticismmentioning
confidence: 99%